Pengaruh Citra Diri dan Kompetensi terhadap Kinerja Pegawai Sekertariat DPRD Kabupaten Ogan Ilir - Weta, Fretty; Sopian, Sopian (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2022)
There is a significant positive effect of Self Image (X1) and Competence (X2) on Employee Performance (Y) at the Secretariat of DPRD Ogan Ilir Regency. The results showed that the value of Fcount shows the number 7.803 which means Fcount > Ftable 2.72 and the significance value of Fcount is 0.000, which means the significance value is less than 0.05. So it can be said that H0 is rejected, which means that the independent variables simultaneously (simultaneously) affect the dependent variable of Employee Performance